Research on the process of non-terrestrial networks for 5G - Zhou Shuqi; Chen Fatang (Dianzi Jishu Yingyong)
The emergence of non-terrestrial networks (NTN) marks a major breakthrough in communication technology. It expands the coverage of terrestrial networks by using satellites and high-altitude platforms, thus providing new solutions for global communications. This paper provides a multi-faceted research of NTN, including the following aspects: Firstly, the basic concepts and importance of NTN are introduced, and the deployment mode, application scenario and working frequency bands of NTN are comprehensively outlined, while different system architectures are described in detail; secondly, the main technical challenges faced by NTN are discussed, and related research results are summarized; finally, the future development of NTN is prospected, and potential technological innovations and development paths are pointed out.